COVID-19: Considerations for Medical Education during a Pandemic - Andjela Arandjelovic (MedEdPublish, 2020)
Clinical placement has been the cornerstone of medical training since the early foundations of the medical profession. The COVID-19 pandemic generates unprecedented challenges for the delivery of medical education, particularly in the setting of 'flatten the curve' public health initiatives to curtail transmission. As the number of cases of COVID-19 increase, hospitals are limiting medical students' attendance at ward rounds, clinics and theatre, representing a fundamental shift in clinical education from the bedside to online formats.